PENGEMBANGAN E-BOOK BERBASIS APLIKASI FLIP PDF CORPORATE EDITION MATERI CERITA FIKSI DAN NON FIKSI SISWA KELAS V SEKOLAH DASAR - Ivan Maulana Saputra; Denna Delawanti C; Dwi Agus Setiawan (STKIP Subang, 2026)
In Indonesian language learning in elementary schools, there is a tendency to use limited teaching materials, especially those focused on textbooks. This can cause students to feel less interested and potentially reduce their enthusiasm in following the learning materials. The purpose of this study was to determine the validity, practicality, and effectiveness of the development of Flip PDF Corporate Edition-based E-Books for fictional and non-fiction story materials for fifth-grade elementary school students. This development research uses the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data analysis in this study uses qualitative and quantitative methods. Based on the results of the assessment of media experts, the percentage was 91.66%, material experts 93.18%, language experts 100%, from the three experts, an average of 94.95% was obtained with the category